Tumor and Tumor-like Lesions in Red Foxes (Vulpes vulpes) from Croatia - Šimun Naletilić; Ivan-Conrado Šoštarić-Zuckermann; Željko Mihaljević (Animals, 2024)
The red fox, found on all continents except Antarctica, occupies diverse habitats. In Croatia, it is an indigenous wild species with a population density of 0.7 animals per square kilometer. While tumors in wild animals from the Canidae family are scarce, the true prevalence and diversity of tumors are likely underestimated due to limited research. So far, a limited number of tumors have been observed among the red fox population, either in their natural habitat or in captivity. As part of the National Rabies Control Program, we examined 1890 red fox carcasses over a four-year period. Our focus was on identifying abnormalities on the skin and internal organs that suggest potential neoplastic proliferation. Five red foxes, three males and two females, were found to have growths resembling potential tumors. Their age distribution spanned from 2 to 7 years. Microscopic investigation revealed two collagenous hamartomas, two Meibomian gland adenomas, and one intra-abdominal teratoma within a cryptorchid testis. This retrospective study aims to provide a comprehensive description of tumor and tumor-like lesions observed in free-range red foxes from Croatia, marking the first research of its kind in Croatia.